2001
DOI: 10.1002/ar.1099
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HNK1 epitope by the cardiomyocytes of the early embryonic chick: In situ and in vitro studies

Abstract: Monoclonal antibody HNK1 reacts with a carbohydrate epitope in cell surface glycoproteins and glycolipids. During development, in various species the HNK1 epitopes are expressed in migrating neural crest cells and in the developing conduction cardiomyocytes. The conduction system is generally thought to be developed from cardiomyocytes, but some investigators have hypothesized that it is derived from the neural crest because conduction myocytes express neural antigens, including HNK1. Using immunohistochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Most of these studies used also additional markers to confirm specificity of expression, thus validating this antibody as a (temporal) marker of the CCS. Indeed, in vitro study on cultured precardiac mesoderm cells (Nakajima et al, ) showed that there are at least three cell types, that is, mesenchymal cells with HNK‐1 positivity, and positive and negative cardiomyocytes. However, the HNK‐1 is not, unlike, for example, some ion channels or gap junction proteins, a functional marker—and indeed is absent from the conduction system in the mouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies used also additional markers to confirm specificity of expression, thus validating this antibody as a (temporal) marker of the CCS. Indeed, in vitro study on cultured precardiac mesoderm cells (Nakajima et al, ) showed that there are at least three cell types, that is, mesenchymal cells with HNK‐1 positivity, and positive and negative cardiomyocytes. However, the HNK‐1 is not, unlike, for example, some ion channels or gap junction proteins, a functional marker—and indeed is absent from the conduction system in the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…The HNK‐1 monoclonal antibody is a marker for early migrating neural crest cells (NCC), but reacts also with structures, which are not derived from the neural crest (Gorza et al, ; Luider et al, ). Human natural killer (HNK)‐1, (the CD57 antigen or LEU7) is expressed as a carbohydrate epitope that contains a sulfoglucuronyl residue in several adhesion molecules of the nervous system (Nakajima et al, ). HNK‐1 epitope is also expressed in a subset of myocytes in the developing cardiac conduction system (CCS), making it a very useful, conserved marker for visualizing the CCS in mammals and birds (Nakagawa et al, ; Chuck and Watanabe, ).…”
mentioning
confidence: 99%
“…The extracellular matrix Tenascin-C, is also associated with cell motility [25] , [26] . Like Ccbe1, Tenascin-C is also expressed in the cardiogenic fields and disappear once the heart fields fuse [41] [44] . However, no distinct phenothype was observed in tenascin-C-null mice [45] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our results indicated that increased c Ccbe1 levels resulted in expansion of Hnk1-expressing domain in both CNC cells and heart tube region, while loss of c Ccbe1 decreased Hnk1 signal mostly in the heart tube region. Hnk1 plays a role in the migration of neural crest cells [25] , [26] , and is normally present in the cardiomyocyte precursor [41] [44] .…”
Section: Discussionmentioning
confidence: 99%